PERUBAHAN PENGETAHUAN, SIKAP, DAN PERILAKU IBU DALAM PEMBERIAN MP-ASI ANAK USIA 6-24 BULAN PADA INTERVENSI PENYULUHAN GIZI DI LUBUK BUAYA KOTA PADANG - Ai Kustiani; Artha Prima Misa (JURNAL KESEHATAN PERINTIS, 2018)
In addition to the problem of deficiency and excess nutrients, Indonesia also have chronic malnutrition problems. Chronic malnutrition is a long-term malnutrition that causes stunting in infants. Several factors that cause the high incidence of stunting include lack of knowledge and inadequate nutrition practice. The purpose of this study was to determine the effect of nutritional counseling on changes in knowledge, attitude and behavior of mothers in the provision of MP-ASI children 6-24 months in Lubuk Buaya 2017. The study design was a quasi-group pretest-posttest experiment with a sample 34 people. Counseling was conducted for 3 times (1x / week). Data collection of knowledge variables, attitudes and practices of mothers were conducted using questionnaires. The results showed that there was a significant change (p <0.05) on the knowledge, attitude and practice of mother in giving MP-ASI after giving nutrition counseling. Therefore, nutritional counseling has an effect on improving mother's knowledge, attitude and behavior in giving of MP-ASI at 6-24 months.